La hoja de ajustes propuesto en auditoria al componente de cuentas y documentos por pagar de un ejercicio económico. - Cassola Rodriguez, Maritza Edith (My University, 2019)
To propose the adjustment sheet, the intangible corrections presented in the balances of Accounts and Documents Payable, applying analytical procedures with the purpose of presenting reasonable financial information, motivated the antecedents of the problem of the companies when preparing the financial statements under International Financial Reporting Standards (IFRS), International Accounting Standards (IAS), and interpretations of IAS, which provides senior management with adequate and timely decision-making, the importance of observing International Standards on Auditing ( NIA), in the analytical procedures that are practiced in the process of the execution of the work, bringing as a novelty this component of the current liabilities, that when solving the problem one is incurred in the career of the accounting profession, delimiting the research to the theoretical framework in the development of it with scientific articles published in indexed journals exposed in the Titling Guide of the Technical University of Machala. The method of investigation carried out was the analytical one, with which the practical exercise was solved, determining two findings described in comments, conclusions and recommendations, immaterial errors and not observing the Ecuadorian Civil Code. Finally, three conclusions of the practical case were presented, contrasting the solved exercise with the theoretical framework.
Para proponer la hoja de ajustes, las correcciones inmateriales presentadas en los saldos de Cuentas y Documentos por Pagar, aplicando procedimientos analíticos con la finalidad de que se presente información financiera razonable, se motivó los antecedentes del problema de las empresas al preparar los estados financieros bajo Normas Internacionales de Información Financiera (NIIF), Normas Internacionales de Contabilidad (NIC), y las interpretaciones a las NIC, lo que aporta a la alta gerencia a una adecuad y oportuna toma de decisiones, la importancia de observar las Normas Internacionales de Auditoría (NIA), en los procedimientos analíticos que se practique en el proceso de la ejecución del trabajo, trayendo como novedad este componente del pasivo corriente, que al resolver el problema se está incurso en la carrera de la profesión contable, delimitando la investigación al marco teórico en el desarrollo de la misma con artículos científicos publicados en revistas indexadas expuestas en la Guía de Titulación de la Universidad Técnica de Machala. El método de investigación llevado a cabo fue el analítico, con lo que se resolvió el ejercicio práctico, determinándose dos hallazgos descritos en comentarios, conclusiones y recomendaciones, errores inmateriales e inobservados el Código Civil ecuatoriano. Finalmente se expuso tres conclusiones del caso práctico, contrastando el ejercicio resuelto con el marco teórico.
Keywords: AUDITORÍA; ESTADOS FINANCIEROS; NORMAS INTERNACIONALES DE CONTABILIDAD; NORMAS INTERNACIONALES DE INFORMACIÓN FINANCIERA